PENGARUH TERAPI MUSIK KLASIK TERHADAP PERUBAHAN GEJALA DAN FUNGSI PADA PASIEN RAWAT INAP SKIZOFRENIA DI RUMAH SAKIT KHUSUS DAERAH PROVINSI MALUKU - Svetlana Solascriptura Lewerissa; Sherly Yakobus; Christiana R. Titaley (Fakultas Kedokteran Universitas Pattimura, 2019)
Schizophrenia is a syndrome with a variety unknown causes and a wide course of disease, as well as a number of consequences that depend on consideration of genetic, physical, and cultural influences. Schizophrenic patients have three symptoms: positive symptoms, negative symptoms, and symptoms of disorganization, which have an impact on the patient's function to interact with family, school, work, environment, religion and social. Classical music therapy is useful for relaxation, perception improvement, concentration, and can increase intrapersonal contact. This study aims to determine the effect of classical music therapy on symptom and function changes in schizophrenic patients hospitalized in the sub-acute section of the Maluku Province Regional Special Hospital. This research is an analytical research with an experimental approach. The subjects were 10 schizophrenic patients who were taken with purposive sampling technique which was included in one group pre test-posttest. Data collection was carried out by using the observation of the Global Assessment of Functioning Scale (GAF Scale) before and after being treated by Ludwig Van Beethoven's Symphony No. 9 classical music in seven sessions for seven times in schizophrenic patients. Symptom and function changes of schizophrenic patients will be compared and analyzed by using the Wilcoxon test. The results found that on average, ten schizophrenic patients had symptoms and functions change measured by GAF Scale scores before classical music treatment was 51-60, but after classical music treatment, there was an increase in GAF Scale score, as much as 50% to 61-70 and 50% to be 71-80. So, it can be conclude that classical music therapy can reduce the symptoms and improve general function in schizophrenic patients hospitalized.